2016
DOI: 10.3389/fnhum.2016.00449
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Postural Control of Stability during Gait Initiation Over Obstacles of Different Height and Distance Made Under Reaction-Time and Self-Initiated Instructions

Abstract: Despite the abundant literature on obstacle crossing in humans, the question of how the central nervous system (CNS) controls postural stability during gait initiation with the goal to clear an obstacle remains unclear. Stabilizing features of gait initiation include anticipatory postural adjustments (APAs) and lateral swing foot placement. To answer the above question, 14 participants initiated gait as fast as possible in three conditions of obstacle height, three conditions of obstacle distance and one obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 45 publications
6
75
0
Order By: Relevance
“…This lack of temporal constraint is unlikely to have affected the use of a ballistic strategy, as it has been demonstrated both for temporally unconstrained steps (Lyon and Day, 1997, 2005) and when initiating gait as quickly as possible (Yiou et al, 2016). It is possible that differences in step duration may have influenced the throws to different targets (Zettel et al, 2002a,b; Yiou et al, 2016). However, this is unlikely to explain our data because although step duration changed with step length, it did not change with step direction (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of temporal constraint is unlikely to have affected the use of a ballistic strategy, as it has been demonstrated both for temporally unconstrained steps (Lyon and Day, 1997, 2005) and when initiating gait as quickly as possible (Yiou et al, 2016). It is possible that differences in step duration may have influenced the throws to different targets (Zettel et al, 2002a,b; Yiou et al, 2016). However, this is unlikely to explain our data because although step duration changed with step length, it did not change with step direction (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the subjects developed adaptive postural strategies in order to reach an equivalent mediolateral stability when the initial body weight distribution was modified. It has been shown that mediolateral stability during gait initiation is mainly regulated by the mediolateral APA and the mediolateral swing foot-placement, i.e., the step width (McIlroy and Maki, 1999; Caderby et al, 2014; Yiou et al, 2016a). In the present study, the step width was not modified between the various experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CoM is never repositioned over the stance foot, mediolateral APA help to minimize the extent to which the body subsequently falls towards the swing-leg side during step execution, i.e., mediolateral instability (Jian et al, 1993; Winter, 1995; Lyon and Day, 1997; McIlroy and Maki, 1999; Rogers et al, 2001; Yiou et al, 2016a). In the present study, the results showed that APA duration, i.e., the time allocated to propel the CoM toward the stance foot, did not differ between the various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The backward centre of pressure shift reflects a strategy to generate the initial propulsive forces necessary to reach the intended centre of mass velocity at the end of gait initiation [3][4][5][6]. The mediolateral (ML) centre of pressure shift reflects a strategy to propel the centre of mass above (or beneath) the forthcoming stance foot in order to maintain ML stability during the swing phase of gait initiation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%